The Role of Social Capital in Facilitating Access to Higher Education for Marginalized Communities in Pakistan: A Qualitative Study - Dawar Awan; Amina Hanif Tarar; Dr. Muhammad Ali Tarar; Hafiz Abdul Rafah Razzaq, (Dialogue Social Science Review (DSSR), 2025)
This qualitative study investigated the role of social capital in facilitating access to higher education for marginalized communities in Pakistan through a phenomenological research design. The study employed purposive sampling to select participants from rural populations, ethnic minorities, and economically disadvantaged families across different provinces. Data collection involved in-depth semi-structured interviews with 30 participants, focus group discussions, and participant observations. Thematic analysis revealed five major themes: family and community networks as educational enablers, religious and cultural capital as bridging mechanisms, mentorship and guidance systems, economic cooperation through social bonds, and institutional trust building. The findings demonstrated that bonding social capital within families and communities provided essential emotional and financial support, while bridging social capital facilitated connections with educational institutions and opportunities. Religious networks emerged as significant facilitators, providing both material support and legitimacy for educational pursuits. However, certain traditional social structures also posed barriers, particularly for female participants. The study revealed that successful educational access required strategic navigation of multiple social networks and the ability to convert different forms of social capital into educational opportunities. These findings contribute to understanding how marginalized communities leverage social resources to overcome structural barriers in Pakistan's higher education system and inform policy interventions aimed at improving educational equity. Keywords: Social capital, higher education access, marginalized communities, Pakistan, educational inequality, qualitative research, social networks.